2013
DOI: 10.1158/0008-5472.can-12-1242
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rearrangements Involving the ALK Gene Reveals a Novel Truncated Form Associated with Tumor Aggressiveness in Neuroblastoma

Abstract: Activating mutations of the ALK gene have been identified in sporadic and familial cases of neuroblastoma (NB), a cancer of the peripheral nervous system, and are thought to be the primary mechanism of oncogenic activation of this receptor in this pediatric neoplasm. To address the possibility that ALK activation may occur through genomic rearrangements as detected in other cancers, we first took advantage of high-resolution arraycomparative genomic hybridization to search for ALK rearrangements in NB samples.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 30 publications
(55 reference statements)
10
51
0
Order By: Relevance
“…In order to investigate the therapeutic efficacy of brigatinib in a neuroblastoma setting we employed several neuroblastoma cell lines, including CLB-BAR (MYCN amplification, ALK (Δ4-11) and amplified, ALK addicted), CLB-GE (MYCN amplification, ALK (F1174V) amplification, ALK addicted), IMR32 (MYCN amplification, WT ALK) and CLB-PE (MYCN amplified, WT ALK) [21,[31][32][33]. We have earlier shown that both CLB-BAR and CLB-GE cell lines are ALK addicted, while IMR32 and CLB-PE are not [34,35].…”
Section: Brigatinib Inhibits Alk Activity and Abrogates Proliferationmentioning
confidence: 99%
“…In order to investigate the therapeutic efficacy of brigatinib in a neuroblastoma setting we employed several neuroblastoma cell lines, including CLB-BAR (MYCN amplification, ALK (Δ4-11) and amplified, ALK addicted), CLB-GE (MYCN amplification, ALK (F1174V) amplification, ALK addicted), IMR32 (MYCN amplification, WT ALK) and CLB-PE (MYCN amplified, WT ALK) [21,[31][32][33]. We have earlier shown that both CLB-BAR and CLB-GE cell lines are ALK addicted, while IMR32 and CLB-PE are not [34,35].…”
Section: Brigatinib Inhibits Alk Activity and Abrogates Proliferationmentioning
confidence: 99%
“…The most frequent substitutions, observed in approximately 85% of mutant ALK in neuroblastoma, are localized within the kinase domain of ALK at the F1174 (mutated to L, S, I, C, or V) and R1275 (mutated to Q or L) hotspots (12,21). In neuroblastoma, ALK can also be activated by genomic amplification (approximately 1%-2% of neuroblastomas) or more rarely following structural rearrangements (22).…”
Section: Introductionmentioning
confidence: 99%
“…In this tumor type, characterized by mutations within the tyrosine kinase of ALK in a subset of samples, truncated ALK proteins with complete skipping of exon 2-3 ( ALK del2-3) and exons 4-11 ( ALK del4-11) of ALK have been described and characterized 24,25 . Different than the EML4-ALK del27-derived protein EML4-ALK T1312fs*0 described herein by us, these truncated extracellular domain proteins led to increased constitutive kinase activity of ALK and transformation potential (i.e., ALK del2-3 and ALK del4-11 were putative driver events).…”
Section: Resultsmentioning
confidence: 99%